Drought Sensitivity of Sugarcane Cultivars Shapes Rhizosphere Bacterial Community Patterns in Response to Water Stress - Liu, Qi; Xie, Sasa; Zhao, Xiaowen; Liu, Yue; Xing, Yuanjun; Dao, Jicao; Wei, Beilei; Peng, Yunchang; Duan, Weixing; Wang, Ziting (Frontiers in Microbiology, 2021)
Rhizosphere bacteria, the main functional microorganisms inhabiting the roots of terrestrial plants, play important roles in regulating plant growth and environmental stress resistance. However, little is known regarding the changes occurring within the internal structure of the root microbial community and the response mechanism of host plants that improve adaptability under drought stress. Herein, we conducted an experiment on two sugarcane varieties with different drought tolerance levels under drought and normal water (control) treatments and analyzed the rhizosphere bacterial community under the different treatments using 16S rRNA high-throughput sequencing. Correlation analysis clarified the influences of various factors on the rhizosphere bacterial community structure. Drought stress significantly reduced the diversity of the bacterial community in the rhizosphere of sugarcane. Interestingly, the bacterial community of the drought-sensitive sugarcane cultivar GT39 changed more significantly than that of the drought-tolerant cultivar ZZ9. In addition, we found that ZZ9 had a higher abundance of drought-resistant bacteria in the rhizosphere under optimal soil water conditions, whereas GT39 accumulated a large number of drought-resistant bacteria only under drought stress. GT39 mainly relied on Actinobacteria in its response to drought stress, and the abundance of Actinobacteria was positively correlated with soil acid phosphatase (S-ACP) and soil acid protease levels. In contrast, ZZ9 mainly relied on Bacilli in its response to drought stress, and the abundance of this class was positively correlated with only S-ACP. In conclusion, drought stress can significantly reduce the bacterial diversity of the sugarcane rhizosphere and increase the abundance of drought-resistant bacteria in the rhizosphere. The high abundance of drought-resistant bacteria in the rhizosphere bacterial community of drought-tolerant cultivars under non-drought stress is an important factor of the high drought adaptability of these cultivars. Moreover, the core drought-resistant bacteria of sugarcane rhizosphere and root exudates jointly affected the resistance of sugarcane to drought.